2016
DOI: 10.1111/raq.12182
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterial subcellular components as immunostimulants in fish aquaculture

Abstract: Aquaculture and fisheries products are expected to play a leading part in addressing the food necessities of the increasing human population. However, in intensive aquaculture, fish are exposed to stress conditions that deteriorate their immune systems, leading to increased disease vulnerability. These disease outbreaks have resulted in production losses and represent one of the key constraints in fish farming. Accordingly, aquaculture disease management efforts have concentrated on the establishment of enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Immunostimulants are biosynthetic compounds which can enhance the nonspecific cellular and humoral defences of aquatic animals (Dawood et al, 2018;Giri et al, 2016;Mohan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostimulants are biosynthetic compounds which can enhance the nonspecific cellular and humoral defences of aquatic animals (Dawood et al, 2018;Giri et al, 2016;Mohan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Immunostimulants are biosynthetic compounds which can enhance the nonspecific cellular and humoral defences of aquatic animals (Dawood et al, 2018; Giri et al, 2016; Mohan et al, 2018). Tussah immunoreactive substances (TIS), which were first obtained from the pupal haemolymph of the Chinese oak silkworm Antheraea pernyi , possess various antibacterial activities, and participate in the removal of invading microorganisms (Huang & Wang, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, intensive aquaculture practices result in stress, poor water quality, poor nutritional status, overcrowding, and sudden changes in temperature. Further, widespread industrial developments have caused deteriorated aquatic environments (Giri et al, 2016a). Typically, antibiotics and chemotherapeutics are used to control diseases in aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since bacterial extracts have been shown to stimulate innate immunity in fish and potentially act as an immunostimulant, it may contribute to the rise of immunoglobulin levels. Giri et al [ 33 ] reported that the rise in immunoglobulin levels is a short-term phenomenon attributable to immunostimulants. Due to the vaccine being at its early development and the current study only wanting to observe its early responses, further study needs to be conducted to determine whether the oral vaccine could provide longer-term protection to the fish.…”
Section: Discussionmentioning
confidence: 99%